Microvascular function in patients undergoing chemotherapy - Sutterfield, Shelbi Lorrae (Kansas State University, 2017)
Adjuvant systemic chemotherapy for the treatment of certain cancers, particularly breast and lymphoma, adversely impacts cardiovascular health. However, the extent to which it impairs endothelial function is not well understood. Therefore, the purpose of this study was to determine if microvascular and macrovascular endothelial-dependent vasoreactivity is attenuated in breast cancer and lymphoma patients currently being treated with chemotherapy compared to healthy counterparts. With laser Doppler imaging, cutaneous microvascular function was evaluated via changes in cutaneous vascular conductance (CVC) in response to iontophoresis of acetylcholine (ACh). Endothelium-dependent flow-mediated dilation (FMD) was evaluated in the brachial artery via ultrasonography. CVC responses to iontophoresis of ACh in the cutaneous microcirculation was significantly lower in cancer patients than in control subjects (cancer (n=7): 959.9 ± 187.3%; control (n=7): 1556.8 ± 222.2%; P = 0.03). Furthermore, FMD was significantly lower in cancer patients than in control subjects (cancer: 2.2 ± 0.6%; control: 6.6 ± 1.4%; P = 0.006). These data provide evidence of microvascular and macrovascular dysfunction in breast cancer and lymphoma patients currently undergoing adjuvant chemotherapy, which may contribute to the increased long-term risk of cardiovascular disease morbidity and mortality in those treated for cancer.
Keywords: Chemotherapy; Endothelial functionCancer